ISOLASI DAN IDENTIFIKASI BAKTERI ENDOFIT PENGHASIL ANTIBAKTERI DARI DAUN TANAMAN BINAHONG (Anredera cordifolia (Ten.) Steenis) - Fenni Nursulistyarini; Erny Qurotul Ainy (Universitas Sebelas Maret, 2014)
Abstract - Plants Binahong (Anredera cordifolia (Ten.) is known as a medicinal plant by the community. Purpose of this study was to obtain endophytic bacteria producing antibacterial isolates from leaves binahong and continued with the characterization and identification of isolates. Antibacterial activity was determined using the paper disc assay method on the media NA is by using the supernatant of endophytic bacteria isolates tested on pathogenic bacteria Escherichia coli ATCC 35216 and Staphylococcus aureus ATCC 29 523. Retrieved 9 bacterial isolates and 3 of them are isolates E5, E7, and E8 was selected as superior isolates were able to inhibit the growth of test bacteria . Results identification of isolates using the matching profile showed that isolates E5, E7, E8 respectively including members of the genus Staphylococcus, Pseudomonas, and Bacillus. Keywords: isolation, identification, endophytic bacteria, binahong (Anredera cordifolia (Ten.)